Computational intelligence methods for bioinformatics and biostatistics 7th international meeting, CIBB 2010, Palermo, Italy, September 16-18, 2010, revised selected papers - CIBB (Meeting) 2010 Palermo, Italy); Rizzo, Riccardo; Lisboa, Paulo J. G.; SpringerLink (Online service). (Berlin, Heidelberg Springer, 2011)
This book constitutes the thoroughly refereed post-proceedings of the 7th International Meeting on Computational Intelligence Methods for Bioinformatics and Biostatistics, CIBB 2010, held in Palermo, Italy, in September 2010. The 19 papers, presented together with 2 keynote speeches and 1 tutorial, were carefully reviewed and selected from 24 submissions. The papers are organized in topical sections on sequence analysis, promoter analysis and identification of transcription factor binding sites; methods for the unsupervised analysis, validation and visualization of structures discovered in bio-molecular data prediction of secondary and tertiary protein structures; gene expression data analysis; bio-medical text mining and imaging methods for diagnosis and prognosis; mathematical modelling and simulation of biological systems; and intelligent clinical decision support systems (i-CDSS).
Electronic reproduction.
Keywords: Bioinformatics -- Congresses; Computational intelligence -- Congresses; Biometry -- Congresses; Electronic books